Perancangan Kartu Permainan Kesenian Ondel-Ondel - Saarani, Daniel; Hidayatullah, Taufan (Fakultas Desain Universitas Komputer Indonesia, 2021)
The art of Betawi culture has a variety of arts, one of which is Ondel-Ondel art without speech in the city area of Jakarta. Ondel-Ondel's artistry is subjected to alterations in Ondel-Ondel, which in the phenomenon of Ondel-Ondel The emergence of other functions used as a pengamen. The determination of this topic aims to emphasize the art information Ondel-Ondel through the media game card games that include the history, functions and essences based on interviews, surveys, questionnaires and literary sources and preserve and maintain the existence of Ondel-Ondel in modern times that not only regarded as a display, but to remain active in arts and performances. In the design of the art topic of Ondel-Ondel which is found that some of the people of Jakarta just know the form of Ondel-Ondel but do not know the function, meaning and history, then in the government and community or craftsmen must work together to maintain the existence of Ondel-Ondel arts and performances.